Fraud as a Social Construction: Qualitative Findings on the Role of Opportunity and Gender Dynamics in Accounting Practices - Wilamsari, Feni; Purwanti, Lilik (Cita konsultindo, 2025)
This study explores fraud as a socially constructed phenomenon shaped by individual experiences, organizational contexts, and gendered dynamics within accounting practices. Using a qualitative interpretive approach, data were gathered through in-depth interviews with auditors, practitioners, and academics to understand how meanings of fraud are formed, negotiated, and enacted. The findings reveal that opportunity remains the most dominant driver of fraudulent behavior, transcending gender boundaries. While participants initially associated fraud cases with male perpetrators due to media representation and structural exposure, the study shows that both men and women share equal potential to commit fraud when opportunities emerge. Gender differences appear not in the propensity to engage in fraud, but in access to roles, visibility, and situational pressures that shape exposure to such opportunities. The study contributes to a deeper understanding of fraud beyond traditional rational-choice models by emphasizing its socio-cultural embeddedness. Implications highlight the need for organizations to address structural factors that create opportunities for fraud and to reconsider gendered assumptions embedded within fraud risk assessments.